Correlation between Family Harmony and Students' Perceptions of Juvenile Delinquency - Arzanah Putri; Herman Nirwana (Jurnal Neo Konseling, 2023)
The background of this research is because students' perceptions of juvenile delinquency are not good, so there are still many students who commit juvenile delinquency. One of the factors that influence students' perceptions of juvenile delinquency is family harmony. This study aims to analyze: (1) students' perceptions of juvenile delinquency, (2) adolescent family harmony, (3) examine and analyze the relationship between family harmony and student perceptions of juvenile delinquency. This research uses a quantitative method with a descriptive correlational type. The population of this study was 601 students enrolled at SMAN 1 Koto Balingka with a sample of 240 students which was determined by stratified random sampling technique. The instruments used were "family harmony checklist" and "student perception checklist about juvenile delinquency". The findings in this study show that: (1) family harmony is in the high category, (2) students' perceptions of juvenile delinquency are in the good category, (3) there is a positive and significant relationship between family harmony and students' perceptions of juvenile delinquency with correlation coefficient of 0.641 and a significant value of 0.000. Implications for Guidance and Counseling can be done by providing information services, individual counseling and group guidance.